Pseudomembranous Aspergillus Tracheobronchitis: Case Report of a Rare Manifestation of Airway Invasive Aspergillosis - Jae Sung Cho; Jeong Jae Kim; Sun Young Jeong; Yun soo Lee; Miok Kim; Sung Joon Park; Myeong Ju Koh (대한영상의학회지, 2022)
Aspergillus tracheobronchitis, an uncommon form of invasive pulmonary aspergillosis, is characterized by the development of a pseudomembrane, ulcers, or an obstruction that is predominantly confined to the tracheobronchial tree. Pseudomembranous Aspergillus tracheobronchitis is the most severe form of Aspergillus tracheobronchitis, and only a few cases have been reported in Korea. We report the characteristic chest CT findings in a patient diagnosed with pseudomembranous Aspergillus tracheobronchitis after bronchoscopy and successfully treated by proper antifungal treatment.